Good governance in national solid waste management policy (NSWMP) implementation: A case study in Kuala Lumpur - Abas, Muhamad Azahar (2017)
National Solid Waste Management Policy (NSWMP) has been introduced as main guideline in Malaysia’s solid waste management. The execution of NSWMP has involves diverse stakeholders which the practice of good governance is a significant requirement to attain the aims of NSWMP. However, the implementation of NSWMP is ineffective because of poor governance. Therefore, this study is conducted to explore the governance of NSWMP in Kuala Lumpur. This research has four (4) research objectives which are to identify the perception of stakeholders in NSWMP governance, to analyse the practices of good governance that implemented by stakeholders, to investigate the constraints of good governance and to develop a good governance framework for effective NSWMP implementation. A convergent parallel strategy is adopted in this study to gather both quantitative and qualitative data in concurrently and to analyse both data separately. A total of 640 respondents were selected through quota sampling method to participate in the quantitative data collection (questionnaire distribution). Besides that, six (6) respondents were selected through purposive sampling method for qualitative data collection (in-depth interview). Descriptive and inferential data analyses were conducted to interpret the quantitative data by using Statistical Package for the Social Sciences (SPSS). Content analysis was adopted to interpret the qualitative data by using NVivo Software. After that, triangulation technique was conducted to develop a good governance framework for NSWMP implementation. In general, the perception of stakeholders on NSWMP governance which based on four main variables (policy clarity, resources management, stakeholder’s competency, implementation system) was moderate. Moreover, this study has found out that the practice of good governance is not a new practice by stakeholders. However, these practices are still insufficient. Accordingly, five (5) constraints of good governance have been identified such as inadequate fund, bureaucratic burden, poor staff competency, poor communication among stakeholders and lack of policy implementation guideline. To address the poor governance issue, this study has developed a good governance framework for effective NSWMP implementation. This framework can improve the decision-making process in NSWMP implementation. Besides that, this framework also enables to enhance the understanding of government and corporate agencies on good governance practice in NSWMP implementation. Basically, this study has given empirical evidence that the good governance theory is applicable for effective NSWMP implementation in Malaysia.